From passivity to the struggle for change: activist aspirations of the youth from the rural regions of Vojvodina - Petrović, Marica; Čikić, Jovana (Sociološki pregled, 2022)
The youth in modern Serbian society is mostly uninterested in activism. That leads to their political atomization, privatization, more pronounced feeling of not belonging, and social exclusion. Since young people in villages are at a higher risk of social exclusion, a question arises as to the nature of their practices and readiness for activism. The analysis of activist aspirations of the village youth was performed on the basis of the data collected by a semi-standardized interview on the sample of 500 respondents (aged 18–29) in ten villages in Vojvodina. The results show that young people encounter numerous problems and are aware of them, but they do not take active part in their resolution. Village youth is characterized by political passivity, accompanied with the negative assessment of the efficiency of own action, as well as the feeling of social weakness.